COMPARATIVE ANALYSIS OF OPERATIONAL EFFICIENCY IN SHARIA BANK SERVICES AND CONVENTIONAL BANKS - Fauzatul Laily Nisa (Cahaya Ilmu Bangsa, 2024)
Currently, competition in the banking industry is becoming increasingly difficult due to increasingly sophisticated domestic banking operations. Talking about banking, there are two types of banks in Indonesia. The first is a conventional bank and the other is a sharia bank. The existence of banks that comply with sharia principles creates competition between banks. Of course, this requires bank management to act very firmly and carefully to improve performance. The form of research used is descriptive analysis and uses a quantitative approach with a literature review. This research was carried out using the official website of the Indonesian Stock Exchange (BEI) http: //www.idx.co.id/ and based on secondary materials. The results of statistical tests imply that important divergences were found in several variables between conventional banks and Islamic banks, such as ROA, BOPO/REO, LDR/FDR, and ROE. However, for the CAR, NIM/NOM, and NPL/NPF variables, no relevant divergence was obtained.